Pedagogical factors that influence efl teaching: some considerations for teachers’ professional development (2013)
In this article we present the results of a qualitative research study on the pedagogical factors that influence English teaching in four public schools of Medellín, Colombia. Twelve teachers were interviewed regarding three linguistic principles: communicative competence, native language effect, and interlanguage. The data analysis led to the identification of various factors, such as teachers’ linguistic ego, view of their teaching role, and attitude towards English, which shape English teaching and are tied to teachers’ education. It was concluded that teachers’ professional development must tap into these factors so teachers can effectively revise their beliefs and adjust their practices to ensure a high qualityin their teaching.En este artículo se presentan los resultados de una investigación cualitativa acerca de los factorespedagógicos que influyen en la enseñanza del inglés en cuatro escuelas públicas de Medellín (Colombia). Doce maestros fueron entrevistados sobre tres principios lingüísticos: competencia comunicativa, efecto de la lengua nativa e interlenguaje. A partir del análisis se concluyó que factores como el ego lingüístico, la percepción del papel del docente y la actitud frente al inglés son determinantes en laenseñanza de esta lengua. Se concluye que dichos factores deben ser incorporados en los programas de desarrollo profesional para que los maestros puedan revisar sus creencias y ajustar sus prácticas efectivamente y así asegurar la calidad de su enseñanza.